Simulation of System Dynamics for Improving The Quality of Paddy Production in Supporting Food Security - Mala Rosa Aprillya; Erma Suryani (Journal of Information Systems Engineering and Business Intelligence, 2023)
Background: The food security policy is an effort to ensure stable food availability and stable access of the community to food. As the population increases, this will affect the fulfillment of food needs in the future. Therefore, increase in rice production is needed to support food security.